Analisa Volume Air Hasil Pemampatan Udara Kompresor Torak Puma Pk-50-160a Terhadap Waktu Loading - Deni Deni; Asep Saepudin (Rekayasa Material, Manufaktur dan Energi, 2020)
The capacity of the air volume in the compressor is reduced due to the presence of water in the compressor tube. Narrowing of the compressor cylinder caused by compressed air can shorten the compressor loading time which results in a reduction in the amount of pressurized air flow required in the pneumatic system. With the knowledge of the volume of water resulting from compressed air, it can easily determine the schedule of disposal of water that is in the compressor tube, so as to maximize the performance of the compressor. This research is a type of quantitative research because it involves calculation of numbers or quantification of data. The technique of collecting data is done by observation. From this research, the volume of water contained in the compressor tube which affects loading time is 27 liters which can shorten the loading time by 0.5 minutes and because water is an incompressible fluid, the compressor tube which was originally 160 liters capacity is reduced to 133 liters. What can be obtained from this research is that the reduced compressor capacity can have an impact on the amount of pressurized air flow in the pneumatic system.